Cetuximab has an inhibitory effect on cell motility in SCC-4 oral squamous cell carcinoma cell line - Furtado, L. M.; da Silveira, I. C.; Carneiro, A. C. D. M.; Zehuri, M. M. O. N.; Carboni, S. S. C. M.; Tavares-Murta, B. M.; Crema, V. O. (Cellular and Molecular Biology, 2017)
Cetuximab is a chimeric monoclonal antibody that acts as a competitive antagonist, by binding to EGFR. This cell signalling pathways regulates tumor progression. The oral squamous cell carcinoma undergoes to regional spreading and distant metastasis. This study aimed to evaluate the effect of treatment with Cetuximab on cell migration and invasion in OSCC cells, by using the SCC-4 cell line. Cell migration and cell invasion assay were performed and actin cytoskeleton of control and treated with Cetuximab cells were evaluated. Differences were considered significant when p<0.05.Cetuximab inhibited the migration of SCC-4 cells at three concentrations: 1 µg/mL, 50 µg/mL and 100 µg/mL (p<0.0001) in a dose-dependent manner. The number of SCC-4 treated cells with 1 Î¼g/mL that migrated through the membrane was statistically different from 50 Î¼g/mL (p<0.001) and 100 Î¼g/mL (p<0.0001), and between 50 Î¼g/mL and 100 Î¼g/mL (p<0.01). Cetuximab 50 Î¼g/mL inhibited cell invasion through the MatrigelTM compared with SCC-4 control cells (p<0.01). Cetuximab 50 Î¼g/mL affected the organization of the actin cytoskeleton. Cetuximab has an inhibitory effect on actin cytoskeleton organization, cell migration and invasion, suggesting that Cetuximab treatment can be important to avoid oral squamous cell carcinoma metastasis.